KUALITAS INFORMASI LAPORAN KEUANGAN ENTITAS SEKTOR PUBLIK DAERAH X - Marsdenia, Marsdenia (Jurnal Vokasi Indonesia, 2016)
This study has objective to analyze factors influencing public sector entity’s financial statement informations quality. Factors examined include quality of human resources, internal control system, information technology utilization and external factors as a moderating variable. Originally RSUD X is Private Hospital namely RS Y Kota A, then, in Mid 2014 have been transformed to be RSUD X as local gorvernment hospital City of A. Metodologi research for this study is Quantitative Research Method by Questionnaires or Surveys approach through respondent for this study is the human resources involved in the functions of accounting, finance and Billing for BPJS and staff who handle in patient account. Respondent in RSUD Bogor totally 42 staffs. The Data collected from questionnaires analyzed by multiple linear regression methods. The Result show that